2019
DOI: 10.1111/iej.13095
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT analysis of chronic apical periodontitis induced by several specific pathogens

Abstract: Aim To conduct three‐dimensional micro‐CT analysis of bone destruction, periapical sclerotic changes and inflammatory root resorption (IRR) to compare the differences between Enterococcus faecalis (Ef)‐ and Porphyromonas gingivalis (Pg)‐induced chronic apical periodontitis (CAP). Methodology Mono‐species bacteria‐induced CAP was established in the first and second molars of the right maxilla and mandible of male Sprague–Dawley rats. Fifteen animals were divided into three groups with five rats in each group: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
2
21
1
Order By: Relevance
“…Using micro-CT to study CAP is a good option, but there is no consistent protocol for analysing CAP in rodents (Kalatzis-Sousa et al, 2017). Parameters found in similar work was used for analysing CAP in rodents (Chen et al, 2019). The results of the micro-CT revealed that P. gingivalis dental infection after pulp exposure induced CAP, with PALs found in 98.2% of the molars.…”
Section: Discussionmentioning
confidence: 99%
“…Using micro-CT to study CAP is a good option, but there is no consistent protocol for analysing CAP in rodents (Kalatzis-Sousa et al, 2017). Parameters found in similar work was used for analysing CAP in rodents (Chen et al, 2019). The results of the micro-CT revealed that P. gingivalis dental infection after pulp exposure induced CAP, with PALs found in 98.2% of the molars.…”
Section: Discussionmentioning
confidence: 99%
“…Although rat apical periodontitis models to investigate endodontic infection have been introduced, most studies have focused on periapical lesions and histologic changes at a specific time point [ 14 , 22 ], and the chronological changes in the microbiota together with radiologic and histologic analyses has been poorly studied. Notably, there are some previous reports available on the induction of murine apical periodontitis by Enterococcus faecalis or Fusobacterium nucleatum [ 23 , 24 ] and rat chronic apical periodontitis by Porphyromonas gingivalis or E. faecalis [ 25 ]. Nonetheless, those reports have seemingly only limited applicability for the comprehensive understanding of the role of microbial communities responsible for the disease progress.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the main goal of the study was to evaluate anti-inflammatory drugs in treatment of apical periodontitis, a histological and histometric evaluation was performed to understand the signalling pathways and mediators involved in bone resorption. Such a method is commonly used to determine periapical bone loss in induced apical periodontitis (De Rossi et al 2008, Paula-Silva et al 2009b, 2016, Cintra et al 2014, but this analysis could be improved through radiographic and tomographic images as discussed elsewhere (Aksoy et al 2019, Chen et al 2019. This lack of radiographic image is one limitation of the present study, which should be better explored in future studies.…”
Section: Discussionmentioning
confidence: 87%
“…2019, Chen et al . 2019). This lack of radiographic image is one limitation of the present study, which should be better explored in future studies.…”
Section: Discussionmentioning
confidence: 99%